A Comparison of Christians' Concepts of Jesus Christ and God. Issue 1 (2nd January 2017) - Cummings, Jeremy P.; Kusner, Katherine G.; Lucero, Steven; Padgett, Emily A.; Gollery, Thomas J.; Pargament, Kenneth I.
ABSTRACT: In the god concept literature, little research has been conducted on how people think about and relate specifically to Jesus Christ. This study addresses the extent to which Christians distinguish between Jesus and God in terms of their concepts of Jesus and God, the pathways they use to connect with Jesus and God, and the benefits they seek and receive from Jesus and God. The study also tests whether participants' concepts of Jesus have unique predictive power for psychological, social, and spiritual criterion variables after controlling for their concepts of God. The sample includes 165 college students and 107 church attendees who self-identified as Christians. Results indicate that although most participants view Jesus and God as being similar to each other, they perceive Jesus to be warmer but less transcendent and stern than God. Including participants' concepts of Jesus in hierarchical multiple regressions accounted for significant additional variance after controlling for their concepts of God in predicting participants' negative affect, social justice attitudes, spiritual emotions, and Christian orthodoxy. Participants generally used various pathways more to connect with God than with Jesus, and they reported seeking and receiving many benefits more from God than from Jesus. These results suggest that future research on god concepts among Christians ought to include separate measures of Jesus concepts and God concepts.